Fluidization expansion of novel generation dense medium and flow regime transition in gas-solid separation fluidized bed - Chenyang Zhou; Yuemin Zhao; Chengguo Liu; Yanjiao Li; Zhonglin Gao; Xuchen Fan; Tatiana Aleksandrova; Chenlong Duan (Fundamental Research)
Gas-solid separation fluidized beds are important for coal cleaning through the removal of ash-forming impurities. Homogeneous fluidization is considered as an ideal separation method because it results in fewer pressure fluctuations and smaller bubbles. And Geldart C ultrafine powder could further intensify the fluidization stability of Geldart A particles. Thus, the present work provides a breakthrough in the density adjustment method in the gas-solid separation field, namely, combining Geldart A magnetite particles and Geldart C fine coal particles as a novel dense medium. The results showed that the addition of ultrafine coal effectively increased the overall expansion of the dense phase by the adhesion of the coal particles on the surfaces of the magnetite particles. To comprehensively understand the difference in the dense phase expansion ratio between the Geldart B/D and Geldart A particles, the flow regime was investigated to determine the transition point of homogeneous expansion using various dense media. The propagation velocities of the shock and continuity waves were analyzed using the theory of elastic systems. A quantitative criterion is proposed to identify the transition point. Based on the error analysis, the available data in the literature and the present work gave an overall in 5 × 10−5 error range compared to the prediction data. Overall, this research provides a comprehensive understanding of homogeneous fluidization characteristics using a novel dense medium and a reliable quantitative transition criterion of the flow regime for Geldart B/D and Geldart A particles in a gas-solid separation fluidized bed.